Early senescence of the oldest leaves of Fe‐deficient barley plants may contribute to phytosiderophore release from the roots. Issue 3 (20th March 2014) - Higuchi, Kyoko; Iwase, Jun; Tsukiori, Yoshifumi; Nakura, Daiki; Kobayashi, Nahoko; Ohashi, Hidenori; Saito, Akihiro; Miwa, Eitaro
<x xml:space="preserve">Abstract</x> Barley (Hordeum vulgare), which tolerates iron (Fe) deficiency, secretes a large amount of phytosiderophores from its roots. However, how barley is able to allocate resources for phytosiderophore synthesis when the carbon assimilation rate is reduced by Fe deficiency is unknown. We previously suggested that the acceleration of senescence in older leaves triggered by Fe deficiency may allow the recycling of assimilates to contribute to phytosiderophore synthesis. In this work, we show the relationship between an increase in the C/N ratio in older leaves and Fe‐deficiency tolerance among three barley cultivars. The increase in the C/N ratio suggests an enhanced capacity for the retranslocation of carbohydrates or amino acids from older leaves to the sink organs. An increase in the sucrose concentration in Fe‐deficient barley also suggests active redistribution of assimilates. This metabolic modulation may be supported by accelerated senescence of older leaves, as Fe deficiency increased the expression of senescence‐associated genes. The older leaves of Fe‐deficient barley maintained CO2 assimilation under Fe deficiency. Barley that had been Fe‐deficient for 3 days preferentially allocated newly assimilated 13C to the roots and nutrient solution. Interestingly, the oldest leaf of Fe‐deficient barley released more 13C into the nutrient solution than the second oldest leaf. Thus, the balance between anabolism and catabolism in older leaves, supported by highly regulated senescence, plays a key role in metabolic adaptation in Fe‐deficient barley.